The Edict of Cyrus and notions of restoration in Ezra-Nehemiah and Chronicles - Gilhooley, Andrew M. (Hebrew Bible monographs, 2020)
Introduction -- Preliminary considerations -- The Edict of Cyrus as a compositional introduction -- The Edict of Cyrus as a compositional conclusion -- The Edict of Cyrus as a canonical conclusion -- Conclusion.